ISLANDERS, PROTESTANT MISSIONARIES, AND TRADITIONS REGARDING THE PAST IN NINETEENTH-CENTURY POLYNESIA*. (4th August 2016) - SMITH, TOM
ABSTRACT: In this article, I consider Polynesian genealogies, which took the form of epic poems composed and recited by specialist genealogists, and were handed down orally through generations of Polynesians. Some were written down in the nineteenth century, reaching an English-speaking audience through a number of works largely neglected by historians. In recent years, some anthropologists have downplayed the possibility of learning anything significant about Polynesian thought through English-language sources, but I show that there is still fresh historical insight to be gained in demonstrating how genealogies came to interact with the traditions of outsiders in the nineteenth century. While not seeking to make any absolute claims about genealogy itself, I analyse a wide body of English-language literature, relating chiefly to Hawai'i, and see emerging from it suggestions of a dynamic Polynesian oral tradition responsive to political, social, and religious upheaval. Tellingly, Protestant missionaries arriving in the islands set their own view of history against this supposedly irrelevant tradition, and in doing so disagreed with late nineteenth-century European and American colonists and scholars who sought to emphasize the historical significance of genealogy. Thus, Western ideas about history found themselves confounded and fragmented by Polynesian traditions.